EP466 Stage II/III endometrial cancer - how RADICAL should we be? A review of management in the northern ireland regional cancer centre. (1st November 2019) - Addley, S; McComiskey, M; Dobbs, S; Nagar, H; Craig, E; Harley, I
Abstract : Introduction/Background: ESGO guidance (2016) recommends simple hysterectomy and lymphadenectomy (PLN/PALN) for stage II and III endometrial cancer. BGCS guidance (2017) also recommends simple hysterectomy in both stage II/III disease, but advises reserving lymph node dissection for stage III only. Methodology: Practice in the Northern Ireland Regional Cancer Centre was compared with current ESGO and BGCS guidance. A retrospective case-note review was performed for patients undergoing surgery for stage II/III endometrial cancer in the NI Regional Cancer Centre between 2013 and 2018. Results: 53 cases were identified, with mean age 60.5 years and mean BMI 30.6 kg/m 2 . 62% of the cohort had stage II endometrial cancer on pre-operative MRI; and 38% stage III. 50% of surgeries were performed by Consultants 'buddy-operating'. All patients underwent radical hysterectomy - 84% laparoscopically, with a conversion to open rate of 6.9%. 96% had concomitant BSO; 94% PLND and 23% PALND. PALND was performed in 25% with pre-operative stage III disease. One case of bowel injury occurred intra-operatively. Histopathology reported parametrial involvement in 19% of pre-operative stage II and 25% of pre-operative stage III cases. Histopathology also identified positive PLN in 19% and 25% of pre-operative stage II and III cases respectively; and positive PALN in 3.8% and 6.3% of these cases. Post-operatively, 7% of patients required HDU. The mean haemoglobin drop was 15 g/dl. Urinary retention was the most common complication (19%). Mean length of stay was 4.9 days. Conclusion: In accordance with current guidance and in light of the higher morbidity associated with a radical approach, a change of practice to simple hysterectomy has been recommended within the unit. The role of lymphadenectomy remains controversial, particularly in stage II disease; a population which may particularly benefit from the introduction of sentinel lymph node sampling in the future. Disclosure: Nothing to disclose.